The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5194/nhess-14-1703-2014
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid model for mapping simplified seismic response via a GIS-metamodel approach

Abstract: Abstract. In earthquake-prone areas, site seismic response due to lithostratigraphic sequence plays a key role in seismic hazard assessment. A hybrid model, consisting of GIS and metamodel (model of model) procedures, was introduced aimed at estimating the 1-D spatial seismic site response in accordance with spatial variability of sediment parameters. Inputs and outputs are provided and processed by means of an appropriate GIS model, named GIS Cubic Model (GCM). This consists of a block-layered parametric stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…The potential criteria influencing local seismic amplification susceptibility were determined through a critical review of literature. By reviewing documents on earthquake engineering, seismology, geology, tectonic and structural engineering, geomorphology, and seismic microzonation reports and guidelines (Fäh et al, 1997;Ding et al, 2004;Molina et al, 2010;Mundepi et al, 2010;Marulanda et al, 2012;Hassanzadeh et al, 2013;FEMA, 2014;Fraume et al, 2014;Grelle et al, 2014Grelle et al, , 2016SM Working Group, 2015;Rehman et al, 2016;Nwe and Tun, 2016;GEM, 2017;CAPRA, 2017;Michel et al, 2017;Trifunac, 2016;Hassanzadeh and Nedovic-Budic, 2016), in total 14 influencing criteria were identified (Table 1).…”
Section: Determining the Relevant Criteria By Reviewing Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The potential criteria influencing local seismic amplification susceptibility were determined through a critical review of literature. By reviewing documents on earthquake engineering, seismology, geology, tectonic and structural engineering, geomorphology, and seismic microzonation reports and guidelines (Fäh et al, 1997;Ding et al, 2004;Molina et al, 2010;Mundepi et al, 2010;Marulanda et al, 2012;Hassanzadeh et al, 2013;FEMA, 2014;Fraume et al, 2014;Grelle et al, 2014Grelle et al, , 2016SM Working Group, 2015;Rehman et al, 2016;Nwe and Tun, 2016;GEM, 2017;CAPRA, 2017;Michel et al, 2017;Trifunac, 2016;Hassanzadeh and Nedovic-Budic, 2016), in total 14 influencing criteria were identified (Table 1).…”
Section: Determining the Relevant Criteria By Reviewing Literaturementioning
confidence: 99%
“…Furthermore, Bouckovalas and Papadimitriou (2005) investigated the influence of slope topography in amplifying the peak horizontal seismic ground acceleration suggesting high amplifications near the crest. Grelle et al (2016) presented formulae for topographic amplification on slope surface. These studies indicated that with the increase in slope angle the amplification factor would increase.…”
Section: B Determining Fuzzy Set and Fuzzification Of Thresholds Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the above-mentioned GIS-based models, Grelle et al (2014) have recently introduced a hybrid model, based on the "GIS cubic model (GCM)" frame which is, in turn, based on the concept of lithodynamic units and zones. Here, a lithodynamic unit is defined as a lithological unit, which is characterized by a shear wave velocity-depth-dependent curve (as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%